PENANGANAN KOMPLAIN DI INSTALASI RAWAT JALAN RUMAH SAKIT UMUM PERMATA BLORA PADA MASA PANDEMI COVID - Fika Jati Kusuma (STIKES Cendekia Utama Kudus, 2022)
Cases of complaints in the outpatient installation of Permata Blora Hospital continue to increase and continue to repeat during the Covid-19 pandemic. The number of complaints that come in requires complaint handling to maintain patient satisfaction. This study aims to determine the handling of complaints from the outpatient installation of Permata Blora General Hospital during the Covid-19 pandemic. This type of qualitative research. Data collection through in-depth interviews with key informants and triangulation of informants. The key informants were five officers. The five officers are responsible for handling complaints in the outpatient installations, and triangulation informants are outpatients who have complained. The data processing and analysis of this research use the method of content analysis. The results showed that complaint handling officers had not received training, the media for submitting complaints was not yet known to the patient, and the team network did not yet exist. This study concludes that the handling of complaints has not been good, marked by untrained human resources, the patient's complaint media is not yet known, and there is no team network.